Konkurencja w warunkach turbulentnego otoczenia - Bembenek, Bogusław (Competitiveness in the Conditions of Turbulent Surrounding, 2006)
In the article some changes of competitiveness paradigm in the conditions of turbulent surroundings are stressed. The author presents a new dimension of competitive culture and underlines that today agreements among competitors within some areas of activities and cooperation rather than the expensive competition that consists in the battle between them are much more profitable. The author stresses the meaning of conception of co-operation in the process of enterprise competitiveness creation. He claims that thanks to such activities the enterprise is directed on the usage of appearing market opportunities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 69-75